2015
DOI: 10.1016/j.jand.2015.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Disruption in the Relationship between Blood Pressure and Salty Taste Thresholds among Overweight and Obese Children

Abstract: Background Prevalence of high blood pressure (BP) among American children has increased over the past two decades, due in part to increasing rates of obesity and excessive dietary salt intake. Objective We tested the hypotheses that the relationships among BP, salty taste sensitivity, and salt intake differ between normal-weight and overweight/obese children. Design In an observational study, sodium chloride (NaCl) and monosodium glutamate (MSG) taste detection thresholds were measured using the Monell two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 42 publications
1
36
0
2
Order By: Relevance
“…However, another study reported that median detection and recognition thresholds for NaCl were within normal limits for both essential hypertension and hypertension due to primary hyperaldosteronism patients (125). Moreover, high systolic blood pressure was associated with elevated NaCl thresholds among normal weight children, but not among overweight/obese children (122). The authors suggested that this apparent disruption in the relationship between salty taste response and blood pressure was influenced by body weight.…”
Section: Systemic Conditions and Medication Effects On Saliva Secretionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, another study reported that median detection and recognition thresholds for NaCl were within normal limits for both essential hypertension and hypertension due to primary hyperaldosteronism patients (125). Moreover, high systolic blood pressure was associated with elevated NaCl thresholds among normal weight children, but not among overweight/obese children (122). The authors suggested that this apparent disruption in the relationship between salty taste response and blood pressure was influenced by body weight.…”
Section: Systemic Conditions and Medication Effects On Saliva Secretionmentioning
confidence: 98%
“…age, gender, obesity status, diet, culture, lifestyle, dose and time using medicine). These differences lead to opposite results, and to date, there is no consensus (122). For example, high blood pressure was found to be associated with higher recognition or detection thresholds for salty taste (123,124).…”
Section: Systemic Conditions and Medication Effects On Saliva Secretionmentioning
confidence: 99%
“…For bitterness there seems to be more stability, as studies found sensitivity for 6-npropylthiouracil (PROP) to be similar between early readers and adults (Anliker, Bartoshuk, Ferris, & Hooks, 1991), and similar for female pre-teens and adults (James, Laing, & Oram, 1997). To my knowledge, there is a lack of literature about the development of children's taste sensitivity with regards to particularly sourness (Liem & Mennella, 2003;Liem, Westerbeek, et al, 2004), but also saltiness (Bobowski & Mennella, 2015;Goldstein & Leshem, 2014;Knof, Lanfer, Bildstein, Buchecker, & Hilz, 2011;Lanfer et al, 2013) and umami (Bobowski & Mennella, 2015;Knof et al, 2011;Lanfer et al, 2013). Developmental differences in taste sensitivity indicate that it could have a different relationship with taste preferences at different times.…”
mentioning
confidence: 99%
“…En diversos estudios se ha evidenciado la relación directa entre factores modificables, como la ingestión elevada de sodio, el sobrepeso y la obesidad, que favorecen la elevación de la presión arterial, y se han encontrado cifras hasta tres veces más elevadas en niños obesos, independientemente de su raza o sexo (6).…”
unclassified
“…La transición en la alimentación es fundamental para establecer hábitos alimenticios saludables; la exposición temprana a alimentos con alto contenido de azúcar y sal se relaciona con su mayor consumo y aumenta el riesgo de enfermedades crónicas en la edad adulta, por lo cual las estrategias de intervención temprana contribuyen a reducir su incidencia (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
unclassified